2019
DOI: 10.1093/nar/gkz554
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric activity of DNA polymerases at and recruitment of exonuclease ExoR and of PolA to the Bacillus subtilis replication forks

Abstract: DNA replication forks are intrinsically asymmetric and may arrest during the cell cycle upon encountering modifications in the DNA. We have studied real time dynamics of three DNA polymerases and an exonuclease at a single molecule level in the bacterium Bacillus subtilis. PolC and DnaE work in a symmetric manner and show similar dwell times. After addition of DNA damage, their static fractions and dwell times decreased, in agreement with increased re-establishment of replication forks. Only a minor fraction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 63 publications
4
42
1
Order By: Relevance
“…We additionally generated functional mVenus fluorescent protein fusions to DnaC and to DnaG, and employed fusions to DnaE and to DnaX, previously shown to be able to functionally replace wild type proteins (43). We found that a fusion of mVenus to the C- Next, we treated cells with concentrations of MMC, HPUra or SHX that led to slowed down growth rate but did not stop growth ( Fig.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…We additionally generated functional mVenus fluorescent protein fusions to DnaC and to DnaG, and employed fusions to DnaE and to DnaX, previously shown to be able to functionally replace wild type proteins (43). We found that a fusion of mVenus to the C- Next, we treated cells with concentrations of MMC, HPUra or SHX that led to slowed down growth rate but did not stop growth ( Fig.…”
Section: Resultsmentioning
confidence: 95%
“…to compare dynamics of replication proteins to those seen after addition of Mitomycin C (MMC), which induces DNA damage supposed to transiently block the progression of forks (11,40,41), or of 6(p-Hydroxyphenylazo)-uracil (HPUra), which reversibly binds to and inhibits DNA polymerase PolC, thereby blocking progression of replication (42).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations